Curriculum, plans, and processes in instructional design : international perspectives - Seel, Norbert M.; Dijkstra, S. (L. Erlbaum Associates, 2004)
This title presents perspectives on the relationship between curriculum research and instructional design, as well as new developments in the use of information and communication technology.